BMC Palliative Care
BMC Palliative Care is an open access journal publishing original peer-reviewed research articles in the clinical, scientific, ethical and policy issues, local and international, regarding all aspects of hospice and palliative care for the dying and for those with profound suffering related to chronic illness.